Executive functions and moral judgment in students of different social and cultural realities: Lima, Huancavelica and Ayacucho - Canales, Ricardo (2017)
The study sought to determine whether there are differences in levels of development of moral judgment and executive neuropsychological functions in students from three public institutions of higher education in the country, considering its diverse social and cultural reality.To examine the Moral Judgment, 48 students from the University of San Marcos, 77 students from the University of Huancavelica and 84 students of the Higher Pedagogical Institute of Ayacucho he was evaluated with a test of moral judgment (adaptation of SROM Gibbs and Widaman) and to examine executive functions, took into account 23 students from the University of San Marcos, 20 of University of Huancavelica and 15 students from the University of Huamanga, examining the battery BANFE executive functions (Flores- Ostrosky, 2012) .The results showed significant differences in the levels of development of moral judgment in favor of the group of Lima, in contrast to the levels reached by the students of Huancavelica.On the other hand, in most dimensions executive Neuropsychological frontal lobe examined, scores also favor the group of students from Lima.In conclusion significant differences between groups of students tested from different socio-cultural realities in their performance in moral judgment and executive neuropsychological functions of the frontal lobe.